MODERN APPROACHES AND INNOVATIONS IN TEACHING MUSIC CULTURE - Kasimjonova Marjona Alisher kizi (Scholars Digest Publishing, 2023)
This article provides detailed information about the role of music culture in the development of our national culture and the formation of students’ abilities and talents by teachers.
Keywords: ability, music, tradition, culture, youth, pedagogy, idea, time, research.